The association between asymptomatic hyperuricemia and knee osteoarthritis: data from the third National Health and Nutrition Examination Survey. Issue 9 (September 2019) - Wang, S.; Pillinger, M.H.; Krasnokutsky, S.; Barbour, K.E.
Summary: Objective: In vitro and clinical studies suggest that urate may contribute to osteoarthritis (OA) risk. We tested the associations between hyperuricemia and knee OA, and examined the role of obesity, using a cross-sectional, nationally representative dataset. Method: National Health and Nutrition Examination Survey (NHANES) III used a multistage, stratified probability cluster design to select USA civilians from 1988 to 1994. Using NHANES III we studied adults >60 years, with or without hyperuricemia (serum urate > 6.8 mg/dL), excluding individuals with gout (i.e., limiting to asymptomatic hyperuricemia (AH)). Radiographic knee OA (RKOA) was defined as Kellgren–Lawrence grade ≥ 2 in any knee, and symptomatic radiographic knee osteoarthritis (RKOA) (sRKOA) was defined as RKOA plus knee pain (most days for 6 weeks) in the same knee. Results: AH prevalence was 17.9% (confidence interval (CI) 15.3–20.5). RKOA prevalence was 37.7% overall (CI 35.0–40.3), and was 44.0% for AH vs 36.3% for normouricemic adults ( p  = 0.056). symptomatic radiographic knee osteoarthritis (sRKOA) was more prevalent in AH vs normouricemic adults (17.4% vs 10.9%, p  = 0.046). In multivariate models adjusting for obesity, model-based associations between AH and knee OA were attenuated (for RKOA, prevalence ratio (PR) = 1.14, 95% CI 0.95, 1.36; for sRKOA, PR = 1.40, 95% CI 0.98, 2.01). In stratified multivariate analyses, AH was associated with sRKOA in adults without obesity (PR = 1.66, 95% CI 1.02, 2.71) but not adults with obesity (PR = 1.21, 95% CI 0.66, 2.23). Conclusions: Among adults aged 60 or older, AH is associated with knee OA risk that is more apparent in adults without obesity.